1976
DOI: 10.1530/jrf.0.0460299
|View full text |Cite
|
Sign up to set email alerts
|

Capillary blood flow to ovarian follicles, stroma and corpora lutea of anaesthetized sheep

Abstract: The radioactive microsphere technique was used to determine the rate of blood flow through vessels of up to 15 mum diameter in the ovaries of 23 anaesthetized sheep in the 72 hr preceding ovulation. The validity of the microsphere technique was established in two preliminary studies. On Days 14, 15 and 16 of the cycle the rate of blood flow (ml.min-1 .100 g-1 tissue) was 1122, 708 and 116 to the CL; 157, 258 and 140 to the stroma; and 627, 742 and 1096 to the follicles, respectively. Blood flow to grossly atre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
1

Year Published

1981
1981
1999
1999

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 8 publications
5
31
1
Order By: Relevance
“…Accompanying rapid growth of the corpus luteum, dynamic changes in luteal vascularity occur throughout the oestrous cycle (Clark, 1900; Andersen, 1926;Basse«, 1943;Bruce and Moor, 1976;Reynolds, 1986;Reynolds et ah, 1992; Zheng et ah, 1993). The mature corpus luteum is highly vascular and receives one of the greatest rates of blood flow, per unit of tissue mass, of any organ (Reynolds, 1986;Niswender and Nett, 1988;Reynolds et ah, 1992Reynolds et ah, , 1994Redmer and Reynolds, 1996;Reynolds andRedmer, 1998, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Accompanying rapid growth of the corpus luteum, dynamic changes in luteal vascularity occur throughout the oestrous cycle (Clark, 1900; Andersen, 1926;Basse«, 1943;Bruce and Moor, 1976;Reynolds, 1986;Reynolds et ah, 1992; Zheng et ah, 1993). The mature corpus luteum is highly vascular and receives one of the greatest rates of blood flow, per unit of tissue mass, of any organ (Reynolds, 1986;Niswender and Nett, 1988;Reynolds et ah, 1992Reynolds et ah, , 1994Redmer and Reynolds, 1996;Reynolds andRedmer, 1998, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…It is reasonable to expect that some reduction of capillary blood flow in follicles undergoing atresia should occur. One possible explanation of the failure of Bruce and Moor (1976) to demonstrate a reduction in thecal blood flow in atretic follicles was the use of anaesthetised animals combined with the low numbers of microspheres retained by individual follicles. A similar technique has been used successfully to describe changes in blood supply to periovulatory follicles in ewes (Murdoch, Nix and Dunn, 1983).…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent ultrastructural studies showed degenerative changes in the thecal capillaries of sheep follicles which were judged to be in the early stages of atresia (O'Shea, . These findings suggested that disruption of thecal capillary blood flow is an early event in atresia and might be responsible for the onset of follicular atresia, Bruce and Moor (1976) obtained measures of capillary blood flow in ovarian follicles of anaesthetised ewes by administering intracardiac doses of one million radioactive microspheres in order to fractionate cardiac output. They concluded that ^lood flow to grossly atretic foUicles did not differ significantly from that to non-atretic follicles of a similar size'.…”
Section: Introductionmentioning
confidence: 99%
“…The capillary bed is less dense in other parts of the theca, and the larger vessels supplying and draining the thecal capillaries are more peripherally situated in and around the theca externa. Follicular blood flow is high, reaching levels comparable to those of functional luteal tissue when calculated per unit weight of tissue in the sheep (Bruce and Moor 1976).…”
Section: Follicular Blood Vessels and Lymphaticsmentioning
confidence: 93%